Lost in Rotation: The Erosion of Tacit Engineering Knowledge in Indonesia’s State-Owned Defense Enterprises - Sriyanto; Aris Sardjito; Sri Murtiana (Yayasan Darussalam Bengkulu, 2026)
Organizations that are heavily focused on engineering depend significantly on tacit engineering knowledge that is built up through experience, practice, and ongoing engagement in intricate technological processes. Although practices such as personnel rotation, workforce mobility, reassignment, and retirement are prevalent in workforce management, they can pose challenges to the continuity of knowledge when essential expertise is not adequately conveyed. This concern is especially pertinent in state-owned defense enterprises, where the retention of accumulated organizational knowledge is crucial for specialized engineering capabilities and lengthy technology development cycles. This research investigated the types of tacit engineering knowledge that are most susceptible to loss, the ways in which personnel rotation leads to knowledge degradation, and the organizational consequences and strategies for knowledge retention related to these dynamics. A qualitative multiple-case study approach was utilized, drawing on secondary documentary data from annual reports, corporate documents, industry reports, government publications, and previous academic research. The analysis concentrated on three Indonesian state-owned defense companies: PT Pindad, PT PAL Indonesia, and PT Dirgantara Indonesia. Thematic analysis and cross-case comparisons were employed to uncover recurring themes. The results reveal that manufacturing know-how, troubleshooting skills, system integration expertise, and accumulated production experience are particularly at risk of erosion. Knowledge discontinuities were linked to personnel reassignment, organizational transfers, retirement, movements related to promotions, and project mobility, particularly when structured transfer mechanisms were lacking. These disruptions were associated with interruptions in capability, ongoing learning initiatives, variations in quality, and inefficiencies in operations. The results underscore the significance of knowledge mapping, succession planning, organized mentoring, practice communities, and knowledge repositories in facilitating the continuity of engineering capabilities. The research concludes that while personnel rotation is not necessarily harmful, engineering-focused organizations might gain from achieving a balance between workforce mobility and systematic approaches that maintain and convey essential tacit engineering knowledge.